Welfare Use in Japan: Trends and Determinants - Suzuki, Wataru; Zhou, Yanfei (Journal of Income Distribution®, 2007)
This article represents the first step in filling a large gap in knowledgeconcerning why Public Assistance (PA) use recently rose so fastin Japan. Specifically, we try to address this problem not only by performinga Blanchard and Quah decomposition on long-term monthlytime series data (1960:04-2006:10), but also by estimating prefecturelevellongitudinal data.Two interesting findings emerge from the time series analysis. Thefirst is that permanent shock imposes a continuously positive impacton the PA rate and is the main driving factor behind the recent increasein welfare use. The second finding is that the impact of temporaryshock will last for a long time. The rate of the use of welfare is quiterigid because even if the PA rate rises due to temporary shocks, it takesabout 8 or 9 years for it to regain its normal level.On the other hand, estimations of prefecture-level longitudinal dataindicate that the Financial Capability Index (FCI) of the local government2and minimum wage both impose negative effects on the PA rate.We also find that the rapid aging of Japan's population presents a permanentshock in practice, which makes it the most prominent contributionto surging welfare use.